2020
DOI: 10.15275/rusomj.2020.0204
|View full text |Cite
|
Sign up to set email alerts
|

Features of cytokine signaling forming T-helper immune response in COPD of varying severity

Abstract: Introduction — Currently, chronic obstructive pulmonary disease (COPD) is a global public health problem. However, molecular mechanisms of the development of this pathology are still poorly understood. The aim is to establish mechanisms of cytokine regulation of T-helper (Th) immune pathway in patients with COPD of varying severity. Material and Methods — The study included 112 patients with stable COPD (mild, moderate and severe grade) and 32 healthy volunteers (control group). We investigated serum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…[32] Aerobic exercise training, which consumes oxygen and energy, can effectively improve diaphragm function and cardiopulmonary endurance, relieve respiratory muscle fatigue, and reduce inefficient ventilation, thereby improving lung function and reducing symptoms such as fatigue and shortness of breath. [34,35] Although the pathogenesis of COPD has not been completely determined, a large number of studies have shown that [36][37][38] immune imbalance in patients with COPD is likely to mediate the expression of inflammatory factors and lead to an inflammatory response, which can lead to the aggravation and deterioration of COPD. It is worth noting that a large amount of CD4+ and CD8+ cell infiltration can be seen in the peripheral airways of lung specimens in patients with COPD, which may be the target of potential intervention therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[32] Aerobic exercise training, which consumes oxygen and energy, can effectively improve diaphragm function and cardiopulmonary endurance, relieve respiratory muscle fatigue, and reduce inefficient ventilation, thereby improving lung function and reducing symptoms such as fatigue and shortness of breath. [34,35] Although the pathogenesis of COPD has not been completely determined, a large number of studies have shown that [36][37][38] immune imbalance in patients with COPD is likely to mediate the expression of inflammatory factors and lead to an inflammatory response, which can lead to the aggravation and deterioration of COPD. It is worth noting that a large amount of CD4+ and CD8+ cell infiltration can be seen in the peripheral airways of lung specimens in patients with COPD, which may be the target of potential intervention therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathogenesis of COPD has not been completely determined, a large number of studies have shown that [ 36 38 ] immune imbalance in patients with COPD is likely to mediate the expression of inflammatory factors and lead to an inflammatory response, which can lead to the aggravation and deterioration of COPD. It is worth noting that a large amount of CD4+ and CD8+ cell infiltration can be seen in the peripheral airways of lung specimens in patients with COPD, which may be the target of potential intervention therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study included smokers and ex-smokers with COPD, and no patient with the predominant Th2 cytokine profile was identified. Accumulating evidence demonstrated that COPD progression is associated with the development of the Th17 immunoregulatory pathway and imbalance between Th17 and Treg cell subpopulations [ 11 13 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%